The Management of Practicing Basketball Games in Physical Education and Sports Lessons to Develop Personality - Carmen I. RĂCHITĂ (Revista de Management Comparat International)
The scientific approach of the theme represents an important step in research activity, with the purpose of interdisciplinary treating between the fundamental domain of athletics and the fundaments of psychology, teaching and sociology. An interdisciplinary approach is necessary taking into consideration the methodical and structural transformations that occur in the contemporary science and a firmer orientation to an interdisciplinary forming of the human personality for his integration in a dynamic democratic society. The personality is a problem that can only be seen in its complexity through a convergence and a careful combination of many points of view (psychology, teaching, sociology, and athletics). But, the interdisciplinary activities have acute formal valances. They contribute to the intercultural, social, emotional and physic development and cultivate the trust in own forces and in competition spirit and many other personality characteristics.